AMPLIFICATION TECHNIQUE OF TRANSLATION IN THE TARGET LANGUAGE NOVEL ‘EARTH DANCE’ - Mahmud, Erlina Zulkifli; Bayusena, Bima; Ampera, Taufik (Universitas Muhammadiyah Semarang, 2021)
This research article discusses the act of adding information called amplification technique in translating Indonesian novel Tarian Bumi into English, ‘Earth Dance’. The amplification technique of translation is needed to fill up the gap regarding the information given in the source language novel and in the target language novel. The language use in the source language novel is so unique that additional information needs to be given in the target language. In that way the readers of the target language will get the same message as the readers of the source language novel. The objectives of this research is to describe what information is added in the target language novel and to identify what background of the adding information through amplification technique of translation. The method used is qualitative method with descriptive-comparative approaches. The data are taken from the Indonesian novel Tarian Bumi which is translated into English, ‘Earth Dance’. The results show that the information added through the amplification technique covers implicit-explicit information, cultural information, and grammatical differences between Indonesian language and English. The background of the application of the amplification technique of translation in this research is the uniqueness of the language use in the source language regarding the setting of the novel, Balinese culture.